Higher skeletal muscle α(2)AMPK activation and lower energy charge and fat oxidation in men than in women during submaximal exercise - Roepstorff, Carsten (Blackwell Science Inc, 2006)
5′AMP-activated protein kinase (AMPK) is an energy sensor activated by perturbed cellular energy status such as during muscle contraction. Activated AMPK is thought to regulate several key metabolic pathways. We used sex comparison to investigate whether AMPK signalling in skeletal muscle regulates fat oxidation during exercise. Moderately trained women and men completed 90 min bicycle exercise at 60% V̇(O(2)peak). Both AMPK Thr(172) phosphorylation and α(2)AMPK activity were increased by exercise in men (∼200%, P < 0.001) but not significantly in women. The sex difference in muscle AMPK activation with exercise was accompanied by an increase in muscle free AMP (∼164%, P < 0.01), free AMP/ATP ratio (159%, P < 0.05), and creatine (∼42%, P < 0.001) in men but not in women (NS), suggesting that lack of AMPK activation in women was due to better maintenance of muscle cellular energy balance compared with men. During exercise, fat oxidation per kg lean body mass was higher in women than in men (P < 0.05). Regression analysis revealed that a higher proportion of type 1 muscle fibres (∼23%, P < 0.01) and a higher capillarization (∼23%, P < 0.05) in women than in men could partly explain the sex difference in α(2)AMPK activity (r = −0.54, P < 0.05) and fat oxidation (r = 0.64, P < 0.05) during exercise. On the other hand, fat oxidation appeared not to be regulated via AMPK. In conclusion, during prolonged submaximal exercise at 60% V̇(O(2)peak), higher fat oxidation in women cannot be explained by higher AMPK signalling but is accompanied by improved muscle cellular energy balance in women probably due to sex specific muscle morphology.